196PThe tolerability and efficacy of FOLFIRINOX in gastro-oesophageal carcinoma. (24th November 2019) - Travers, N; Dean, A; Armstrong, K; Peeperkorn, L; Tan, M; Das, A
Abstract: Background: 5-FU based regimens represent the gold standard of therapy for gastroesophageal carcinomas. Options include Cisplatin-5FU doublets, FOLFOX and FOLFIRI, and in the neo-adjuvant setting FLOT is emerging as a popular choice for those with good performance status. We identified two cohorts of patients who received m-FOLFIRINOX as first line treatment of gastroesophageal carcinoma; patients undergoing neo-adjuvant therapy in whom FLOT was thought to be too toxic, and those with extensive metastatic disease where it was thought that they would not be fit enough for second line therapy. In these settings there is a theoretical advantage to FOLFIRINOX as it exploits the synergy between Oxaliplatin and Irinotecan; Oxaliplatin forms platinum-DNA adducts and Irinotecan prevents the repair of these adducts impeding the development of platinum resistance. We prospectively evaluated our single institution use of FOLFIRINOX in both neo-adjuvant and advanced treatment of gastro-oesophageal carcinomas. Methods: 14 patients with oesophageal, gastro-oesophageal junction or stomach carcinoma gave informed consent to treatment with FOLFIRINOX. Five of these patients had extensive metastatic disease at diagnosis. Response to treatment was recorded via combined CT/PET scanning, endoscopy reports, tumour markers and pathology. Results: All nine patients being treated neo-adjuvantly displayed a good metabolic response prior to surgical resection. Of note was one patient who received only two cycles, however achieved reduction in his tumour from T3N2 to T2N0, which was then completely resected. For the five patients with extensive disease, all showed complete metabolic responses on PET, after having an average of 10.6 cycles each of FOLFIRINOX treatment. Only one patient relapsed 6 months after completing treatment, who subsequently responded to FOLFIRINOX retreatment, and died 23 months after diagnosis. Conclusions: FOLFIRINOX appears to be highly effective in the treatment of early stage and metastatic gastro-oesophageal adenocarcinomas, as well as showing an excellent pathological response rate which aids surgical resection. This case series suggest that the regimen should be formally trialled, comparing tolerability and efficacy against FLOT. Legal entity responsible for the study: St John Of God Hospital Subiaco. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.